A unicorn in monoceros: the 3 M⊙ dark companion to the bright, nearby red giant V723 Mon is a non-interacting, mass-gap black hole candidate. Issue 2 (1st May 2021) - Jayasinghe, T; Stanek, K Z; Thompson, Todd A; Kochanek, C S; Rowan, D M; Vallely, P J; Strassmeier, K G; Weber, M; Hinkle, J T; Hambsch, F-J; Martin, D V; Prieto, J L; et al.
ABSTRACT: We report the discovery of the closest known black hole candidate as a binary companion to V723 Mon. V723 Mon is a nearby (d460 pc ), bright ( V ≃ 8.3 mag), evolved ( T eff, giant ≃ 4440 K, and L giant ≃ 173 L⊙ ) red giant in a high mass function, f ( M ) = 1.72 ± 0.01 M⊙, nearly circular binary ( P = 59.9 d, e ≃ 0). V723 Mon is a known variable star, previously classified as an eclipsing binary, but its All-Sky Automated Survey, Kilodegree Extremely Little Telescope, and Transiting Exoplanet Survey Satellite light curves are those of a nearly edge-on ellipsoidal variable. Detailed models of the light curves constrained by the period, radial velocities, and stellar temperature give an inclination of 87.0^° ^+1.7^° _-1.4^° , a mass ratio of q ≃ 0.33 ± 0.02, a companion mass of M comp = 3.04 ± 0.06 M⊙, a stellar radius of R giant = 24.9 ± 0.7 R⊙, and a giant mass of M giant = 1.00 ± 0.07 M⊙ . We identify a likely non-stellar, diffuse veiling component with contributions in the B and V band of 63 per cent and 24 per cent, respectively. The SED and the absence of continuum eclipses imply that the companion mass must be dominated by a compact object. We do observe eclipses of the Balmer lines when the dark companion passes behind the giant, but their velocity spreads are low compared to observed accretion discs. The X-ray luminosity of the system is L_X7.6× 10^29 ergs s^-1, corresponding to L / L edd ∼ 10 −9 . The simplest explanation for the massive companion is a single compact object, most likely a black hole in the 'mass gap'.